Performant Mutation Identification Using Targeted Next‐Generation Sequencing of 14 Thoracic Aortic Aneurysm Genes. Issue 8 (13th June 2015) - Proost, Dorien; Vandeweyer, Geert; Meester, Josephina A.N.; Salemink, Simone; Kempers, Marlies; Ingram, Christie; Peeters, Nils; Saenen, Johan; Vrints, Christiaan; Lacro, Ronald V.; Roden, Dan; Wuyts, Wim; et al.
<x xml:space="preserve">Abstract</x> Thoracic aortic aneurysm (TAA) is an important cause of death in the industrialized world. Both syndromic and non‐syndromic forms of TAA exists and to date 14 causative genes have been identified. To shorten the turnaround time, increase mutation‐uptake and reduce the overall cost of molecular testing, we developed a next generation sequencing panel of 14 TAA genes (ACTA2, COL3A1, EFEMP2, FBN1, FLNA, MYH11, MYLK, NOTCH1, SKI, SLC2A10, SMAD3, TGFB2, TGFBR1 and TGFBR2) that can be tested simultaneously.